Observation of binding and polymerization of Fur repressor onto operator-containing DNA with electron and atomic force microscopes. - Le Cam, E (1994)
The Fur (ferric uptake regulation) protein is a global regulator that, in the presence of Fe2+, represses the expression of a number of iron-acquisition genes and virulence determinants such as toxins. Dark-field electron microscopy of positively stained Fur-DNA complexes in addition to atomic force microscopy allowed direct visualization of Fur interactions with the regulatory regions of aerobactin and hemolysin operons and provided complementary information about the structure of the complexes. According to the DNA used and the protein/DNA ratio, Fur binding to DNA results in partial or total covering of the fragments, indicating that the protein initiates polymerization along the DNA molecules at specific sites. Negative staining of Fur-DNA complexes revealed a well-ordered structure of the polymer suggesting a helical arrangement. Local rigidification of the DNA molecules resulting from Fur binding could be involved in the repression process.